Archival Science International Journal on Recorded Information - Anderson, Karen; Oliver, Gillian; Yakel, Elizabeth; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Archival Science aims at promoting the development of archival science as an autonomous scientific discipline, targeting primarily on researchers and educators in archival science, and secondarily on everyone else who is professionally interested in recorded information. The scope of the journal is the whole field of recorded process-related information, analysed in terms of form, structure and context. The journal's approach is integrated, interdisciplinary and intercultural: it covers the whole records continuum; it associates with the scientific disciplines dealing with the function of records and the way they are created, preserved and retrieved, the context in which information is generated, managed and used and the social and cultural environment of records creation in different times and places; it acknowledges the impact of different cultures on archival theory, methodology and practice, by taking into account different traditions in various parts of the world, and by promoting the exchange and comparison of concepts, views and attitudes in those traditions.
Keywords: Cultural heritage; Library science; Information storage and retrieval; Application software; Anthropology; Library Science; Computer Appl. in Arts and Humanities; Cultural Heritage; Information Storage and Retrieval; Anthropology